DETERMINAN PERILAKU KECURANGAN AKADEMIK MAHASISWA AKUNTANSI SEBAGAI CALON AKUNTAN (Studi Empiris Pada Mahasiswa Akuntansi Unisma dan UIN Malang) - Lisdiana Lisdiana; Afifudin Afifudin; Hariri Hariri (Universitas Islam Malang, 2022)
This research was conducted with the aim of knowing the determinants of student academic fraud behavior through the variables of pressure, opportunity, rationalization, ability and competitiveness. The population of this study were students majoring in accounting, Islamic University of Malang and UIN Malang class of 2018. The sample determination used the Slovin formula and the number of respondents was 82 students. This research uses multiple linear regression model. The results showed that pressure, rationalization and competitiveness had no effect on students' academic fraud behavior. Meanwhile, opportunity and ability have a positive effect on student academic fraud behavior.Keywords: academic fraud behavior, pressure, opportunity, rationalization, capability, competitiveness